Mapeamento de práticas socioagroecológicas com uso do sistema de informação geográfica - VILHENA, Maria da Graça Moia (2023)
From the industrial revolution to the use of nuclear energy, human actions have intensified environmental problems. In Brazil, the consequences caused by the unrestrained use of natural resources can already be felt in several regions, with increased rainfall, soil impoverishment and loss of biodiversity. Farmers from different places are already looking for strategies to deal with these climate changes. With the adoption of geographic information systems, it is possible to monitor areas at risk and predict future impacts. From this, the objective of this work was to execute the functions and basic notions of a geographic information system to identify and describe practices adopted by social agents in the face of climate change. The research was developed in four municipalities in the northeast of Pará, Abaetetuba, Acará, Igarapé-Miri and Tailandia. And through the application of questionnaires and semi-structured interviews, it was possible to identify and describe the strategies adopted by the farmers. In addition, using the UTM Geo map and TimeStamp applications and the Google Earth pro and QGIS (Quantum GIS – Geographic Information System) software, it was possible to show, on the maps, the locations of the experiences observed in the research.